Population Studies and Carrageenan Properties in Eight Gigartinales (Rhodophyta) from Western Coast of Portugal - Pereira, L. (2013)
Eight carrageenophytes, representing seven genera and three families ofGigartinales (Florideophyceae),were studied for 15months. The reproductive status, dry weight, and carrageenan content have been followed by a monthly random sampling. The highest carrageenan yields were found in Chondracanthus acicularis (61.1%), Gigartina pistillata (59.7%), and Chondracanthus teedei var. lusitanicus (58.0%). Species of Cystocloniaceae family produces predominantly iota-carrageenans; Gigartinaceae family produces hybrid kappa-iota carrageenans (gametophytic plants) and lambda-family carrageenans (sporophytic plants); Phyllophoraceae family produces kappa-iota-hybrid carrageenans. Quadrate destructive sampling method was used to determine the biomass and line transect. Quadrate nondestructive sampling method, applied along a perpendicular transect to the shoreline, was used to calculate the carrageenophytes cover in two periods: autumn/winter and spring/summer. The highest cover and biomass were found in Chondrus crispus (3.75%–570 g/m2), Chondracanthus acicularis (3.45%–99 g/m2), Chondracanthus teedei var. lusitanicus (2.45%–207.5 g/m2), and Mastocarpus stellatus (2.02%–520 g/m2).